Palynofloral associations before and after the Permian–Triassic mass extinction, Kap Stosch, East Greenland - Schneebeli-Hermann, Elke; Hochuli, Peter A; Bucher, Hugo (Elsevier, 2017)
The Permian–Triassic boundary (PTB) interval is known to document a major biodiversity crisis in the history of life. It is generally accepted that this crisis had a significant impact on marine invertebrates. The consequences for terrestrial ecosystems are still controversially discussed. Based on palynological analysis we present a high time resolution microfloral succession of the expanded Late Permian (Wuchiapingian)–Early Triassic (Dienerian) section from Kap Stosch, East Greenland. The quantitative distribution of palynomorphs (range charts and relative abundance data) allows for the differentiation of six distinct palynofloral associations. Ammonoids and conodonts provide independent age control for these assemblages. The Wuchiapingian association I, documented from the Ravnefjeld Formation, shows a typical Late Permian assemblage dominated by bisaccate and monosaccate pollen grains and Vittatina spp. It is separated from association II, present in the basal part of the Wordie Creek Formation, by an important hiatus. This association of Changhsingian or earliest Griesbachian age is characterised by the common occurrence of Ephedripites spp. and reduced abundance and diversity of Vittatina spp. Association III, dated as Griesbachian by the presence of ammonoids, is marked by high relative abundances of taeniate bisaccate pollen grains and high spore diversity. A distinct floral break occurs between the gymnosperm dominated Permian and Griesbachian floras and the lycopsid spore dominated Dienerian associations IV–VI. Ammonoid occurrences verify a Dienerian age for the latter associations. Association V is marked by the absence of non-taeniate bisaccate, striate monosaccate pollen grains, and Vittatina spp. Aratrisporites spp. a typical Triassic lycopsid spore occur consistently from this level onwards. Association VI is characterised by highest lycopsid spore abundances. Cluster analysis demonstrates that Griesbachian assemblages (associations II?–III) are similar to Permian ones and clearly differ from ...